O Museu Portuense, um projecto pedagógico - Emília Ferreira (Midas: Museus e Estudos Interdisciplinares)
Porto, 1833. Rewarding personal efforts and spilling of blood, king Pedro IV – while still on the battlefield - rewarded his followers, and all those capable of enhancing the liberal power, with nobility titles. All this happened while he was under siege, stationed in the city of Porto. It was then that the idea of granting a symbolic medal to the population, through the creation of an art museum, crossed his mind. Such a place would glorify the new institutional power. In this way was born the first public art museum in Portugal, the Museu Portuense, developed with a clear pedagogical programme. The establishment was not intended to answer all of the nation’s artistic and cultural needs, but it certainly helped, creating a place where scholars and art lovers could cultivate themselves. Such was the dream of its organizer and first director, João Baptista Ribeiro, a name to remember in Portuguese museology.